Primary Production of Lowland Natural Grasslands and Upland Sown Pastures Across a Narrow Climatic Gradient - Durante, Martín (2017)
Variation in aboveground net primary production (ANPP) is usually studied across wide environmental gradients focusing on spatial averages of zonal natural communities. We studied the spatial and temporal variation of ANPP of upland sown pastures and lowland natural grasslands across a narrow gradient of precipitation and temperature. The Flooding Pampa (Argentina) encompasses an 850–1000 mm range of mean annual precipitation and a 13.8–16.0°C range of mean annual temperature. For 15 100 × 100 km cells, we obtained mean monthly precipitation, temperature, and paddock-level ANPP of upland pastures and lowland grasslands during 8 years. Mean annual ANPP of lowland grasslands and upland sown pastures was positively related to mean annual precipitation. ANPP of upland pastures was 60–80% larger and increased more steeply with mean annual precipitation. ANPP seasonality also changed across the gradient. In lowland grasslands, as mean annual precipitation increased, ANPP monthly maximum increased, minimum decreased, and the duration of the growing season shortened. In contrast, in upland pastures, ANPP monthly maximum was constant, minimum increased, and the growing season lengthened with increasing precipitation. ANPP was more stable across years for lowland grasslands than for upland pastures. The response of annual ANPP to current-year precipitation decreased across the gradient, while the importance of the previous-year precipitation increased. In summary, we found strong spatial and temporal patterns of ANPP across a narrow environmental gradient. In addition, landscape position and species composition heavily influenced those patterns.